A Study Of Parklet Planning, Design And Planting Criteria Examples In Izmır And Istanbul - Yücel Caymaz, Gökçen Firdevs; Zerriouh, Mohammed Abderraouf (Street Art & Urban Creativity, 2024)
The objective of this study is to research the planning, design, planting and maintenance requirements of a quality parklet by means of the examples of Izmir and Istanbul parklets in Turkey. In this regard, planning and design (important elements=wheel stops, flexible posts, raised platform/recommended elements=open guarded-railing, the sub-structure/urban furniture=flooring, seating, lighting, bicycle stands, shades, art, signage), as well as planting and maintenance were tested on two example parklets with a checklist created using on-site detection, photography and observation methods. As a result of the research in question, it was concluded that the use of reflective surfaces and wheel stoppers critical for safe usage are insufficient in parklet designs; that vertical elements don’t meet the minimum usage standard; that there are no lighting, trash, art and game elements in neither area; and that it was determined the Istanbul parklet example was insufficient in terms of shade and planting compared to the Izmir example.